Evaluation of Annual Sediment Load Production in Kenyir Lake Reservoir, Malaysia - Khairul Amri Kamarudin, Mohd; Abd. Wahab, Noorjima; Fadhli Mamat, Ahmad; Juahir, Hafizan; Ekhwan Toriman, Mohd; Firdaus Nik Wan, Nik; Marcus Ata, Frankie; Ghazali, Adiana; Anuar, Atikah; Hafiz Md Saad, Muhammad (International Journal of Engineering and Technology, 2018)
Kenyir Lakeâ€™s natural environment experienced significant changes over the past 20 years. Pressure from anthropogenic activities such as deforestation, construction, and sand mining around Sungai Terengganu, tourism, farming and agricultural has creating imbalance between environmental processes and response in Kenyir Lake. The aim of the study is to estimate the production of sediment yield (Muatan Sedimen) (MS) (tonnes/km2/year) in Kenyir Lake Basin. 21 sampling stations were chosen along Kenyir Lake to represent the upstream and downstream. The statistical analysis proved that the correlation and regression relationship between Total Suspended Solid (TSS), MS and area of catchment. MS showed a weak correlation and insignificant relationship of regression caused by the anthropogenic factors and uncertain climate changes. These sedimentation problems due to unsustainable land use changes, river bank erosion problems and active construction activity around the Kenyir Lake Basin. This study suggests the sedimentation management methods including land use settlement, cliff erosion problems, settlement and negotiable of uncontrolled development operations in Kenyir Lake and the integrated of river and lake management methods based on Integrated River Basin Management (IRBM) in Kenyir Lake Basin is recommended.Â Â